ASSESSMENT OF PERSONAL FINANCE MANAGEMENT AMONG TRANSPORT LOGISTICS STUDENTS' - Ginavičienė, Jurgita; Sprogytė, Indrė; Preikšaitis, Juras (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article presents the results of quantitative research carried out with 305 Vilnius Technologies and Design College transport logistics students in Lithuania. The research focused on the students’ personal financial management. During 2016 the practical training they filled out an electronic demographic data form online and evaluated their personal financial management. The results revealed that transport logistic students assume personal responsibility for their personal financial management. They have short-term goals –at a profitable period to accumulate resources for periods when revenues are not sufficient. The maximum amounts of transport logistic students costs involved food, stationary expenses, presents, taxes.